Isolation, characterization and pathogenicity of fungal pathogens causing post-harvest spoilage in syzygium malaccense (malay apple) - Daud, Alawiah (2016)
Syzygium malaccense (Malay apple) is one of Malaysia’s local fruit that has demands from the local and international consumers. However, post-harvest spoilage of S. malaccense is causing economic loss to exporters in general and local sellers in particular. In addition, spoilage caused by pathogenic microbes may cause health hazards to the consumers. Therefore, in order to curb post-harvest spoilage, the identity of the causal pathogens are crucial for spoilage management. Thus, the objectives for this study were i. To isolate and identify the fungal pathogens at species level from S. malaccense obtained from the local markets in Peninsular Malaysia, ii. To conduct phylogenetic relationship among species, and iii. To perform pathogenicity test. In order to achieve these objectives, the samples were obtained from local fruit markets in four different states namely Negeri Sembilan, Kelantan, Terengganu and Selangor. These samples were subjected to isolation step on Potato Dextrose Agar (PDA) prior to cultural and morphological identification based on visibility and microscopic characteristics of each pure culture isolated. This was then followed by molecular identification, where genomic DNA was extracted and amplified using ITS 1 and ITS 4 universal primer sets and the polymerase chain reaction (PCR) products of each isolate subjected to sequencing and later BLAST analysis based on GenBank sequence database. Finally, pathogenicity test was conducted to confirm the isolated fungal pathogens as the causal agent of the post-harvest spoilage of S. malaccense. Consequently, in the present study the isolated pathogens were identified as Lasiodiplodia theobromae, Pestalotiopsis microspora, and Penicillium verruculosum. In conclusion, all identified fungal pathogens exhibited host-specificity rather than location specific as the causal of post-harvest spoilage of S. malaccense.